Auxílio-reclusão no ordenamento Jurídico brasileiro - Furukawa, Marcia Uematsu (2006)
This work is about the benefit of reclusion-aid foreseen in the General Regime of Social Security. For a better comprehension of this benefit, it was analyzed the Social Welfare as a whole, from the beginning of its development to its modern aspect. The Social Welfare arose with the Constitution of 1988, as a tool of the Social Order in search of social justice and well being, becoming concrete through the subsystems of health, social assistance and social security. In the chapter that describes the Social Security, it is studied the characteristics of this subsystem, as well as the protection that it gives to the family of the insured, which includes the benefit of reclusion-aid. Through a historical summary of this benefit, it is demonstrated that the reclusion-aid is not new in our judicial system; it has been appearing in welfare laws since the 1950 s and became a constitutional rule with the Constitution of 1988. Despite the criticism against the benefit, it is among the several protection measures enacted by the constitutional legislator in accordance with the aims of the Social Security. The benefit is studied with the analysis of the protected risk, the influence of the work activity to establish the conception of risk/necessity and the alterations brought by Law 10666/03. There are still some comments about the alterations brought by the Constitutional amendment no. 20/98, which limited the benefit for the dependents of the insured with low income, considering the constitutional principles of uniformity and equivalence of benefits, selectivity, and distributiveness. Some law cases about this question were also taken into account. In the end, there are some brief considerations about collective protection, through the public civil action in issues of social security, highlighting the importance of this tool, especially for the maintenance of the equity of the group of insured and dependents, in a way that similar issues can be decided uniformly